2015
DOI: 10.1093/eurheartj/ehv353
|View full text |Cite
|
Sign up to set email alerts
|

How does coronary stent implantation impact on the status of the microcirculation during primary percutaneous coronary intervention in patients with ST-elevation myocardial infarction?

Abstract: AimsPrimary percutaneous coronary intervention (PPCI) is the optimal treatment for patients presenting with ST-elevation myocardial infarction (STEMI). An elevated index of microcirculatory resistance (IMR) reflects microvascular function and when measured after PPCI, it can predict an adverse clinical outcome. We measured coronary microvascular function in STEMI patients and compared sequential changes before and after stent implantation.Methods and resultsIn 85 STEMI patients, fractional flow reserve, corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 27 publications
4
94
1
1
Order By: Relevance
“…10/H0408/24) 13, 14, 15, 16. Witnessed verbal assent was obtained from eligible patients after coronary reperfusion in the cardiac catheterization laboratory, and written informed consent was obtained on the ICU, in accordance with the principles of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…10/H0408/24) 13, 14, 15, 16. Witnessed verbal assent was obtained from eligible patients after coronary reperfusion in the cardiac catheterization laboratory, and written informed consent was obtained on the ICU, in accordance with the principles of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…De Maria et al showed that 60% of patients presented with a pre-stenting index of microcirculatory resistance (IMR) higher than 40, suggesting the presence of pre-procedural MVO. 31 In this group, the total ischemic time was longer, infarct size measured by the troponin test was larger, and more patients had a TIMI flow 0 at presentation. Onethird of patients had evidence of impaired microvascular function after a revascularization procedure with an IMR of >40 after stent implantation.…”
Section: Index Of Microcirculatory Resistancementioning
confidence: 76%
“…PPCI with stenting is the conventional gold standard treatment for patients with STEMI, but nearly one third of patients experience suboptimal myocardial reperfusion after stenting of the epicardial coronary segment. 29 Such a condition is well known as slow/no reflow and microvascular impairment is recognized as the pathophysiological mechanism. Stenting has been identified as a procedural step possibly associated with most of DE of athero-thrombotic debris thus contributing to the majority of the microvascular injury.…”
mentioning
confidence: 99%
“…This is particularly relevant if considered that thrombotic burden is well recognized as an important risk factor for post-stenting microvascular injury in STEMI. 29 For this reason deferred stenting is anticipated to be effective mainly in case of large thrombotic burden which probably should be an inclusion criterion in future studies specifically designed to address the benefit of this approach. 11 However, each of the three RCTs available on this topic failed to address this important aspect.…”
mentioning
confidence: 99%
See 1 more Smart Citation